THE QUALITY ASSURANCE OF TEACHING AND LEARNING IN THE FACULTY OF BUSINESS AND ECONOMIC IN UNIVERSITI PENDIDIKAN SULTAN IDRIS - Ismail, Khalid; Gadar, Kamisan; Yeop Yunus, Nek Kamal (International Business Education Journal, 2009)
The Higher Education Institutions (HEIs) are forced to improve their quality of service due to certain reasons. This includes the declining of graduates quality, stiff competition and the pressure of statutory and funding bodies. In order to ensure the quality of HEIs product they choose the certification of ISO 9000:2000. The purpose of the study is to determine the academic management and teaching and learning evaluation are fulfill the ISO 9000:2000 and to examine all activities and processes in teaching and learning are meet specified requirements set by statutory bodies and stakeholders. The sample consists of 100 undergraduate students who are studying in the FBE. A structured of 50 closed ended items questionnaires were used to collect the data. This study uses descriptive statistic. The finding confirms that FBE has the entire requirement set by ISO 9000 and met the standard set by statutory bodies and stakeholders.